Alternative Caregiving Figures and their Role on Adult Attachment Representations. (13th December 2012) - Zaccagnino, Maria; Cussino, Martina; Saunders, Rachel; Jacobvitz, Deborah; Veglia, Fabio; Leonardi, Matilde; Quintas, Rui; Raggi, Alberto
<x xml:space="preserve">Abstract</x> Background The present work represents the first Italian study investigating whether and how mothers who describe unloving experiences with both parents during childhood could become more secure as adults (termed earned‐secures). Method The sample consisted of 94 women from northern Italy. All the subjects were administered the Adult Attachment Interview (AAI) and fill in a screening test evaluating depressive symptoms. Results No significative differences were found regarding depressive symptomatology across the different attachment classifications. The majority of the samples (84%) remember an important alternative support figure during childhood (before 12 years old). Earned‐secures significantly differ from continuous‐secure and insecure groups (F = 27.202; p ≤ 0.01) on the amount of the emotional support from the main alternative support figure and on the average amount of emotional support across alternative support figures (F = 10.44; p ≤ 0.01). The majority of alternative support figures (80%) were grandparents. Conclusions A corrective emotional experience allows the subject to work through his negative childhood experiences and acquire modalities of interaction that enable him/her to function more effectively in the world. The clinical implications of this study will be discussed. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message Attachment theory. Clinical implications of attachment experiences. Corrective emotional experience.